2019
DOI: 10.1177/1753425919872818
|View full text |Cite
|
Sign up to set email alerts
|

Association between IL-6 polymorphisms and sepsis

Abstract: The aim of the present study was to determine whether IL-6 polymorphisms correlate with sepsis. According to the inclusion criteria, the association of IL-6 polymorphisms with sepsis was searched in databases and analysed using comprehensive meta-analysis software. A total of 16 studies were included in this meta-analysis. There was no significant association between the IL-6-174G/C polymorphism and sepsis risk in the total population (C vs. G: OR = 1.04, 95% CI = 0.79–1.38; CC vs. GG: OR = 0.86, 95% CI = 0.53… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 30 publications
0
17
0
3
Order By: Relevance
“…Whereas, NLR only reflects the change in the quantity of immune cells instead of functional change. As a crucial member of inflammatory cytokines, interleukin-6 (IL-6) can be produced by multiple immune cells and plays a pivotal role in host responses to infections by regulating immune function ( 20 – 22 ). Accordingly, combining NLR with IL-6 might potentially enhance the ability to predict the death risk of patients with sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas, NLR only reflects the change in the quantity of immune cells instead of functional change. As a crucial member of inflammatory cytokines, interleukin-6 (IL-6) can be produced by multiple immune cells and plays a pivotal role in host responses to infections by regulating immune function ( 20 – 22 ). Accordingly, combining NLR with IL-6 might potentially enhance the ability to predict the death risk of patients with sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…IL-1 inhibits myocardial contractility by stimulating nitric oxide synthetase (NOS) [29]. IL-6, another proinflammatory cytokine, is also involved in the pathogenesis of sepsis and is considered to be a better predictor of sepsis than TNF-α [30]. Previous studies have shown that miRNAs exhibit important effects on LPS-induced sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…In consequence, this results in tissue and organ impairment, and clinically the development of syndromes such as disseminated intravascular coagulation (DIC), adult respiratory distress syndrome (ARDS), or MODS [ 20 ]. It is worth mentioning that the following factors play an important role in SIRS pathogenesis: microorganism virulence, injury extensiveness, comorbidities in the patient, or gene polymorphism responsible for production of cytokines and other effectors of the immune response [ 10 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a new approach to the SIRS concept, one of the main factors determining the development of the systemic inflammatory reaction and its further course is, among others, an individual susceptibility to develop sepsis affected by gene polymorphism, concerning, e.g., Toll-like receptors, cytokines (TNF-α, TNF-β, IL-1), or clotting factors [ 21 , 29 , 30 , 31 , 32 ]. These studies are aimed at revealing a relationship between a genotype determined by the examined gene polymorphism and severity and the further course of SIRS.…”
Section: Discussionmentioning
confidence: 99%